h ( h ( n ) ) + h ( n + 1 ) = n + 2
Consider all functions h : N → N satisfying the functional equation above for all natural numbers n .
Find the value of h ( 2 0 1 4 ) .
Hint : Try to find some initial values and then somehow try to bring the Golden Ratio into use. Golden Ratio is 2 1 + 5 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did not go nearly as in depth! But great problem! It's a bit confusing though in your solution, you should probably use ϕ for the golden ratio. :D
We can also take h(n)=an+b and solve for the values of a and b..
May be it would be better to mention that zero is not in your natural number set , since there is no agreement on it , 2- Where can I find similar questions ?
Log in to reply
The answer doesn't depend on it. There are few more cases to check but h ( 0 ) = 1 and the rest of the sequence as above is the only solution.
Another equivalent solution is h ( n ) = ⌈ ϕ n ⌉
How did it was first found ,that it can be solved by golden ration ?
Log in to reply
The recurrence relation followed by f ( n ) = [ n ϕ ] is
f ( 1 ) = 1 , f ( n + 1 ) = f ( n ) + 2 if f ( f ( n ) − n + 1 ) = 2 and f ( n + 1 ) = f ( n ) + 1 , otherwise.
If one knows this recurrence relation, this problem can be easily solved.
Problem Loading...
Note Loading...
Set Loading...
Putting n=1 in the functional equation we get h ( h ( 1 ) ) + h ( 2 ) = 3
This shows h ( 2 ) ≤ 2 and h ( h ( 1 ) ) ≤ 2
Suppose h ( 2 ) = 1 and h ( h ( 1 ) ) = 2
Put h ( 1 ) = k so that h ( k ) = 2 .Taking n = 2 in the functional equation we get h ( h ( 2 ) ) + h ( 3 ) = 4
We thus see h ( 3 ) = 4 − h ( 1 ) = 4 − k . Since h ( 3 ) ≥ 1 , we conclude k ≤ 3
If k = 1 ,then we get 2 = h ( h ( 1 ) ) = h ( k ) = h ( 1 ) = k = 1 contradiction
By putting k = 2 , 3 you will get similar contradictions.
We conclude that h ( 2 ) = 1 and h ( h ( 1 ) ) = 2 is not possible
So, h ( 2 ) = 2 and h ( h ( 1 ) ) = 1 and hence h ( 3 ) = 4 − h ( h ( 2 ) ) = 2 .
Inductively we get h ( 4 ) = 5 − h ( h ( 3 ) 0 = 5 − h ( 2 ) = 5 − 2 = 3 ,
h ( 5 ) = 6 − h ( h ( 4 ) ) = 6 − h ( 3 ) = 4
h ( 6 ) = 7 − h ( h ( 5 ) ) = 7 − h ( 4 ) = 4 and so on . See that h ( n ) ≥ 2 for n ≥ 2
Suppose h ( 1 ) = k ≥ 2 .Then 3 = h ( h ( 1 ) ) + h ( 2 ) = h ( k ) + 2 ≥ 2 + 2 = 4 which is impossible.
Thus h ( 1 ) = 1 and h ( 2 ) = 2
We claim that h ( n ) = [ n ϕ ] − n + 1 where ϕ = 2 1 + 5
Lemma 1 . For any natural number n , [ ϕ ( [ n ϕ ] − n + 1 ] = n o r n + 1
Proof [ ϕ ( [ n ϕ ] − n + 1 ] < ϕ ( n ϕ − n + 1 = n ( ϕ 2 − ϕ ) + ϕ = n + ϕ < n + 2
and [ ϕ ( [ n ϕ ] − n + 1 ] > ϕ ( n ϕ − 1 − n + 1 ) − 1 = n ( ϕ 2 − ϕ ) − 1 = n − 1
Lemma 2 For all natural numbers n , [ ( n + 1 ) ϕ ] = [ n ϕ ] + 2 if [ ϕ ( [ n ϕ ] − n + 1 ] = n and [ n ϕ ] + 1 , otherwise
Proof Suppose [ ( n + 1 ) ϕ = [ n ϕ ] + 1 .Then we get
[ ϕ ( [ n ϕ ] − n + 1 ] = [ ϕ ( [ ( n + 1 ) ϕ ] − n ) ] > ϕ ( ϕ ( n + 1 ) − 1 − n ) − 1 = n
so that [ ϕ ( [ n ϕ ] − n + 1 ) ] = n + 1 by lemma 1.On the other hand it can be easily proved if
[ ( n + 1 ) ϕ ] = [ n ϕ ] + 2 , then [ ϕ ( [ n ϕ ] − n + 1 ) ] = n
Suppose the claim is true for 1 ≤ j ≤ n
h ( n + 1 ) = n + 2 − h ( h ( n ) ) = n + 2 − h ( [ n ϕ ] − n + 1 ) = n + 2 − [ ϕ ( [ n ϕ ] − n + 1 ) ] + ( [ n ϕ ] − n + 1 ) − 1 , since [ n ϕ ] − n + 1 < 2 n − n + 1 = n + 1
This reduces to h ( n + 1 ) = [ n ϕ ] + 2 − [ ϕ ( [ n ϕ ] − n + 1 ) ]
Suppose n is such that [ ϕ ( [ n ϕ ] − n + 1 ) ] = n . Then we have [ ( n + 1 ) ϕ ] = [ n ϕ ] + 2 and hence h ( n + 1 ) = [ ( n + 1 ) ϕ ] − n
Considering the other possibility, you will also get h ( n + 1 ) = [ ( n + 1 ) ϕ ] − n
This completes our induction step.
So, h ( 2 0 1 4 ) = [ 2 0 1 4 ϕ ] − 2 0 1 4 + 1 = 3 2 5 8 − 2 0 1 4 + 1 = 1 2 4 5